Optimalisasi Model Paludikultur Sebagai Mata Pencaharian Untuk Meningkatkan Kesejahteraan Petani di Lahan Gambut Kabupaten Oki Sumatera Selatan - Pusvita, Ema; Mulyana, Andy; Adriani, Dessy; Antoni, Mirza (Universitas Galuh, 2024)
Peatland restoration cannot be separated from balancing ecological functions and the needs of community life. Empowering farmers is the initial capital for a peat restoration program with a 3R strategy (rewetting, revegetation, revitalization) that can be carried out appropriately. This balancing concept is useful for environmental sustainability and also the livelihoods of local peat communities. The aim of this research is to analyze the optimization of the paludiculture model as a livelihood to improve the welfare of farmers in the peatlands of South Sumatra. This research uses a survey method conducted in Ogan Komering Ilir (OKI) Regency, one of the four priority districts for peat restoration in South Sumatra Province. Data analysis uses an optimization model, namely maximum income and profit, optimal land use and labor, analyzed using a Linear Programming model with land, capital and labor constraints. The results of the research show that the balance of peatland ecosystem functions must be harmonized with maintaining sources of livelihood that can be carried out by generations of farming communities, namely the need to optimize community income by implementing the paludiculture model which provides optimal benefits obtained from the third scenario, agrosilvofishery, agrisilviculture and agroforestry, which is from the Scenario The third has an optimal profit in the agroforestry scenario of IDR. 71,629,870/year.